Geometrical characteristics of sugarcane bagasse for being used as fuel in fluidized bed technologies - Perez, Nestor Proenza; Travieso Pedroso, Daniel; Blanco Machin, Einara; Antunes, Julio Santana [UNESP]; Tuna, Celso Eduardo [UNESP]; Silveira, Jose Luz [UNESP] (Elsevier B.V., 2019)
Sugarcane bagasse is used as energy source in the sugar cane industry. An appropriate characterization of their physical and morphological properties is vitally important for their use in the gasification and combustion processes. This work makes a study of the size and shape distribution of the bagasse generated in a sugarcane mill based upon two important factors that influence their physical properties, such as aspect ratio (AR) and sphericity. The distribution of the grain sizes has been determined for the analyzed samples; the shapes of the particles has been determined by a manual method and through an image-analysis method, using the Image) software. It has been observed that sugarcane bagasse has a larger length than the other analyzed biomasses, with an almost similar width. The aspect ratio was between 2.14 and 5.5 for all the studied size ranges (9.5-0.15 mm). For particles with diameters smaller than 0.3 mm, the aspect ratio has a similar behavior to the other biomasses, with a reported value of 2.5. The determined sphericity was between 0.27 and 0.558, with a mean value of 0.397. (C) 2019 Published by Elsevier Ltd.
Keywords: Particle shape; Sphericity; Sugar cane bagasse; Aspect ratio; Image analyses